2020
DOI: 10.3390/ijms21207490
|View full text |Cite
|
Sign up to set email alerts
|

Brain Branched-Chain Amino Acids in Maple Syrup Urine Disease: Implications for Neurological Disorders

Abstract: Maple syrup urine disease (MSUD) is an autosomal recessive disorder caused by decreased activity of the branched-chain α-ketoacid dehydrogenase complex (BCKDC), which catalyzes the irreversible catabolism of branched-chain amino acids (BCAAs). Current management of this BCAA dyshomeostasis consists of dietary restriction of BCAAs and liver transplantation, which aims to partially restore functional BCKDC activity in the periphery. These treatments improve the circulating levels of BCAAs and significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 141 publications
(186 reference statements)
1
36
0
Order By: Relevance
“…S2 online), we compared THA rats with Wistar rats, which had no other phenotypic differences. As expected, while the expression of BCAT1, a peripheral nervous system-specific isoform 22 , 23 , was increased, that of BCKDK and the phosphorylation levels of BCKDHA were lower in the hippocampi of THA rats compared to Wistar rats (Fig. 2 b).…”
Section: Resultssupporting
confidence: 80%
“…S2 online), we compared THA rats with Wistar rats, which had no other phenotypic differences. As expected, while the expression of BCAT1, a peripheral nervous system-specific isoform 22 , 23 , was increased, that of BCKDK and the phosphorylation levels of BCKDHA were lower in the hippocampi of THA rats compared to Wistar rats (Fig. 2 b).…”
Section: Resultssupporting
confidence: 80%
“…Moreover, suppression of BCAA catabolic enzyme expression led to reduced cell proliferation and BCAA accumulation in liver carcinogenesis but not in regenerating liver tissues (Ericksen et al, 2019 ). BCKAs can be metabolized by BCKDH to branched-chain acyl-CoA, and blocking this step causes serious metabolic disorders, such as maple syrup urine disease (Xu et al, 2020 ) and propionic academia (Chen et al, 2017 ). Branched-chain acyl-CoA can be further metabolized in several steps to the TCA cycle, and intermediates, such as acetyl-CoA and/or succinyl-CoA, can be used for energy production (She et al, 2007 ) or acetylation modification (Campbell and Wellen, 2018 ).…”
Section: Amino Acid Metabolism In Cancermentioning
confidence: 99%
“…Many studies had also confirmed that this metabolic pathway was abnormal in a variety of diseases, like diabetic kidney disease ( Tao et al, 2020 ), neurodegeneration ( Zizioli et al, 2015 ), Vogt–Koyanagi–Harada ( Xu et al, 2021 ), et al Valine, leucine, and isoleucine, namely, branched-chain amino acids (BCAAs), which could over-induce oxidative processes and up-regulate proinflammatory factors ( Zhenyukh et al, 2017 ), are unable to be synthesized by animals. Hence, a variety of pathological changes, such as maple syrup urine disease (MSUD) ( Xu et al, 2020 ), type 2 diabetes ( Zeng et al, 2019 ), and cancer ( Peng et al, 2020 ; Sivanand and Vander Heiden, 2020 ) could be detected when there is a disorder in BCAA metabolism. Nevertheless, the molecular mechanisms of BCAAs involved in the pathogenesis of RVO-ME-inducing retinopathy remain unknown, thus warranting future research.…”
Section: Discussionmentioning
confidence: 99%